Punch biopsies shorten time to clearance of high-risk human papillomavirus infections of the uterine cervix - Petry, K. U. (BMC Cancer, 2018)
BACKGROUND: The primary objective was to determine human papilloma virus (HPV) clearance rate after cervical biopsy among women with persistent high-risk HPV infection compared with spontaneous HPV clearance rate in the absence of biopsy. METHODS: We collected data from a dedicated screening program of women aged 30–70 years old. Inclusion criteria for the baseline non-interventional cohort were a positive HPV test (hybrid capture 2, HC2) and normal cytology. In the baseline cohort women were followed with approximately yearly HPV-tests and cytology until HPV regressed (one negative HPV test) or interventions in the form of diagnostic biopsies or therapy. Women who had a diagnostic biopsy were included in the biopsy cohort and followed until HPV regression or therapy. Observed HPV regression rates and time to HPV regression were compared between baseline and biopsy cohorts. For the comparison, we used Fisher’s exact test for the HPV regression rates and interval-censored, accelerated failure time model for time to HPV regression. RESULTS: Among the 1079 women included in the baseline cohort, 499 (46.3%) had HPV clearance and 475 were referred for colposcopy with biopsy. The biopsy cohort comprised all women who were not treated and had at least one HC2 test after biopsy (201/475; 42.3%). Of those, 138 (68.7%) experienced HPV regression. In the biopsy cohort, time to clearance of HPV infection was approximately halved (0.46, 95% CI 0.38–0.56) compared with the baseline cohort. This result was robust in a wide range of sensitivity analyses. CONCLUSIONS: A higher proportion of women cleared their HPV infection, and time to HPV clearance was shorter in the biopsy cohort than in the baseline cohort. It is reassuring for clinicians to know that conservative management of patients with HPV persistency is successful when colposcopy with biopsies excludes high-grade disease.